2018
DOI: 10.1038/s41598-018-34622-1
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study Reveals How E64 Approaches, Binds to, and Inhibits Falcipain-2 of Plasmodium falciparum that Causes Malaria in Humans

Abstract: Plasmodium falciparum malaria, which degrades haemoglobin through falcipain-2 (FP2), is a serious disease killing 445 thousand people annually. Since the P. falciparum’s survival in humans depends on its ability to degrade human’s haemoglobin, stoppage or hindrance of FP2 has antimalarial effects. Therefore, we studied the atomic details of how E64 approaches, binds to, and inhibits FP2. We found that E64 (1) gradually approaches FP2 by first interacting with FP2’s D170 and Q171 or N81, N77, and K76; (2) binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…(Figures 3 and 4). This shows that the CC2 has comparatively less binding toward 3BPF compared to E64, as it blocks more catalytic residues like N‐38, N‐81, H‐174, C‐42, Q‐171, C‐39, G‐40 and G‐82 (Salawu, 2018). The results also show the CC2 has got significant binding toward FP‐2 through Cys 42 binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Figures 3 and 4). This shows that the CC2 has comparatively less binding toward 3BPF compared to E64, as it blocks more catalytic residues like N‐38, N‐81, H‐174, C‐42, Q‐171, C‐39, G‐40 and G‐82 (Salawu, 2018). The results also show the CC2 has got significant binding toward FP‐2 through Cys 42 binding.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure is also available in Protein data bank as 3BPF. The E64 proceeds toward FP-2 and binds with it tightly and inhibit it (Salawu, 2018).…”
mentioning
confidence: 99%
“…The high docking score and strong interaction via multiple non-covalent bonds resemble with the binding energy, −31.659 kcal/mol and glide emodel energy −37.219 kcal/mol. E-64 has also shown binding with Falcipain-2 of P. falciparum via hydrogen bonding and electrostatic interactions [37]. Another cysteine protease inhibitor, Leupeptin hemisulfate, has also shown significant docking score (−7.08 kcal/mol) and binding energy (−44.461 kcal/mol) and it is interacting with Trp1084 via hydrogen bond along with Q1241 and D1246 residue.…”
Section: Resultsmentioning
confidence: 99%
“…Several inhibitors were designed based on the interactions of the FP2 and the active site inhibitor E64. Molecular dynamics (MD) simulations indicated that two sets of residues, namely, recruiter groups A (rgA) and B (rgB) (rgA (D170, Q171, C168, G169, A151, and G230); rgB (K76, N77, and N81)) of FP2 are primarily involved in the initial binding with E64 about 80% and 14% of the time, respectively, before finally proceeding to bind with the active site residues [16]. Efforts elsewhere have focused on selective inhibition of falcipains rather than indiscriminate inhibition including its human host cathepsin isoforms.…”
Section: Hemoglobin Hydrolysismentioning
confidence: 99%